1974
DOI: 10.1149/1.2402005
|View full text |Cite
|
Sign up to set email alerts
|

The Formation of Monolayer Metal Films on Electrodes

Abstract: The two-and three-dimensional nucleation and the metal ion adsorption process are discussed as initial steps for electrocrystallization on the same or on a foreign substrate. The metal ion adsorption takes place in the underpotential range, which is more positive than the equilibrium potential of the nucleated metal/metal ion electrode. Thermodynamic considerations show that an overlapping of disturbing processes in the underpotential range can be characterized by a factor ZE, which is called charge-coverage c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
40
0
1

Year Published

1986
1986
2008
2008

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 170 publications
(43 citation statements)
references
References 60 publications
2
40
0
1
Order By: Relevance
“…They also argued that the fact that measured charges in many UPD systems correspond just to a monolayer [42] is strong evidence for the lack of crystallisation process taking place, which would be more dependent on pretreatment of electrodes and purity of solutions. However, the surface coverage corresponding to a complete adsorbed layer are dependent on whether adsorbed atoms are restricted to interstitial sites between surface atoms in the electrode or whether a close-packed structure.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…They also argued that the fact that measured charges in many UPD systems correspond just to a monolayer [42] is strong evidence for the lack of crystallisation process taking place, which would be more dependent on pretreatment of electrodes and purity of solutions. However, the surface coverage corresponding to a complete adsorbed layer are dependent on whether adsorbed atoms are restricted to interstitial sites between surface atoms in the electrode or whether a close-packed structure.…”
Section: Introductionmentioning
confidence: 99%
“…In addition the possibility of phase transformations occurring within the UPD monolayer during the underpotential deposition process was introduced and discussed. However, the work of some other authors [57][58][59][60][61][62][63] performed in the same systems, which soon followed, disputed these conclusions and showed that some of the peaked i-t transients could alternatively result from adsorption processes, although the experimental results were more or less confirmed. The main objection was that no really conclusive evidence for phase transformation through 2D nucleation and subsequent crystal growth.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These early results were perhaps limited in scope, but clearly showed that monolayer deposition at underpotentials results from a strong interaction between the monolayer and the substrate, which may be modelled empirically as an activity less than unity for the deposit, Lorenz used a twin electrode thin~layer (TTL) cell to study UPD [68], where the working and generator electrodes are 50 microns apart and have independent potential regulation. The reference and counter electrodes are held in a separate reservoir with supporting electrolyte.…”
Section: Thus the Levich Equation Nomentioning
confidence: 99%